PENGEMBANGAN VARIASI MENGAJAR DALAM MENINGKATKAN MOTIVASI BELAJAR - ARIANTI Arianti (Adaara: Jurnal Manajemen Pendidikan Islam, 2018)
Abstract. This journal discusses the development of variations in teaching in increasing learning motivation. The learning process is an activity that involves an individual (physical and spiritual), learning activities are never carried out without a strong motivation or motivation from within the individual or from outside the individual who participates in learning activities. Therefore, the learning process requires the development and use of variations in teaching to generate student motivation. Variations in teaching include variations in teaching styles, variations in media and materials, and variations in teaching and learning interactions. Motivation has a very important role in learning activities, there is no learning activity without motivation, therefore motivation has a strategic role in achieving the goals or results of learning. Keywords: Development Of Teaching Variations and Motivation to Learn